Work Ethic of Butonese Women in The West Coast of Seram Island, Maluku - nur aisa hamid hamid; Dwia Pulubuhu; Hasbi Hasbi (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
The article aims to explain Butonese women work ethics focusing on three factors, namely the development of work ethics, the aspects, and the challenges in developing their businesses. The research is a qualitative research with case study. The study is conducted in four villages in Luhu Hoamual District and West Seram District in Maluku Province, including Temi, Tapinalo, Mangge-mangge, and Eli. The informants were the Butonese women whose professions are traders. The methods used in this research are observation, interview and library research. The data analysis was done through reduction, presentation and concluding processes. This study found that the work ethic of Butonese women is not due to a religious calling as Weber said, but as a rational choice following Coleman ideas of surviving from the nature challenges, business opportunities, and family’s economic condition. In this process, two professions with different orientations were born. The pajibujibu sell their agricultural and plantation products from the west coast of Seram in Ambon city, meanwhile, the papalele sell fishery products on the west coast of Seram and the Hitu peninsula. If papalele is easy to get access to capital for business development, pajibujibu finds challenges to get it. Therefore, pajibujibu finds difficult to develop the business in compared to papalele. Nevertheless, both play important roles as actors in the economy of coastal communities.